2014
DOI: 10.1051/0004-6361/201423464
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of a galaxy cluster hidden behind the Galactic bulge using the VVV survey

Abstract: Context. S uzaku and Chandra X-ray observations detected a new cluster of galaxies, Suzaku J1759−3450, at a redshift z = 0.13. It is located behind the Milky Way, and the high Galactic dust extinction renders it nearly invisible at optical wavelengths. Aims. We attempt here to confirm the galaxy cluster with near-infrared imaging observations and to characterize its central member galaxies. Methods. Images from the VVV survey were used to detect candidate member galaxies of Suzaku J1759−3450 within the central… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
5
22
0
Order By: Relevance
“…Other X-ray detections were obtained by Lopes de Oliveira et al (2006), who discovered Cl 2334+48 at z = 0.271 in the Zone of Avoidance in the XMM-Newton archive, and by Mori et al (2013), who detected the rich cluster Suzaku J1759-3450 at z = 0.13 behind the Milky Way bulge. The latter cluster was then confirmed by Coldwell et al (2014), based on infrared data. ered in X-rays by Johnston et al (1981), who identified the 4U 1708 − 23 X-ray source with a cluster of galaxies, and more or less simultaneously at optical wavelengths by Wakamatsu & Malkan (1981) during a search for highly absorbed Galactic globular clusters.…”
Section: Introductionmentioning
confidence: 68%
“…Other X-ray detections were obtained by Lopes de Oliveira et al (2006), who discovered Cl 2334+48 at z = 0.271 in the Zone of Avoidance in the XMM-Newton archive, and by Mori et al (2013), who detected the rich cluster Suzaku J1759-3450 at z = 0.13 behind the Milky Way bulge. The latter cluster was then confirmed by Coldwell et al (2014), based on infrared data. ered in X-rays by Johnston et al (1981), who identified the 4U 1708 − 23 X-ray source with a cluster of galaxies, and more or less simultaneously at optical wavelengths by Wakamatsu & Malkan (1981) during a search for highly absorbed Galactic globular clusters.…”
Section: Introductionmentioning
confidence: 68%
“…Another interesting feature of these CMDs is the branch of very dim and red sources that appears at magnitudes fainter than K s > 16 and colors J−K s > 1.3 (Z−K s > 2.3). These sources can be associated with background galaxies, as some studies suggest (Lucas et al 2008;Coldwell et al 2014;Baravalle et al 2018), although at the faintest magnitudes this sequence is expected to be heavily contaminated with the tail of Galactic stars with higher photometric errors. We note that this sequence is more noticeable in the K s vs J − K s CMD, while the previously mentioned BHB sequence manifests more clearly in the K s vs Z − K s CMD.…”
Section: Cmds Of the Galactic Bulge Fields In The Vvvmentioning
confidence: 99%
“…650) by analyzing their size and colors. Later, Coldwell et al (2014) obtained the photometric properties for the galaxy cluster Suzaku J1759-3450 at z=0.13 in the b261 tile (l=356°. 597, b=−5°.321).…”
Section: Introductionmentioning
confidence: 99%